Efecto de la putrescina y el IBA en la formación de raíces adventicias en estacas de yerba mate - Molina, Sandra Patricia; Sapa, Germán A.; Gallardo, Roque; Radovancich, Anita; Mathot, Mariana; Mayol, Ramon Marcelo (Universidade Regional Integrada do Alto Uruguai e das Missões (URI), 2022)
Poster